Evaluation Of Online Learning And The Impact On Learning Achievement And Student Satisfaction - Tarida Marlin Surya Manurung (Forum Dosen Indonesia, 2022)
The Covid-19 pandemic has had a considerable impact on education systems throughout the world, including Indonesia. The education system must adapt, from an offline learning system to an online learning system. This results in the emergence of several impacts that affect the success and satisfaction of students. There are a number of challenges in implementing online learning in developing countries, both in terms of limited facilities and the readiness factor of human resources, both lecturers and students.. The purpose of this study was to determine the impact of the online learning system on learning success and student satisfaction. The data collection method used in this study is a survey research method. The population and samples taken were students of IBI Kesatuan, Faculty of Informatics and Tourism from semester one to semester five. Data processing and analysis methods were carried out quantitatively and descriptively. The results showed that the online learning system had a positive influence on student success in terms of the value obtained, however there were also twenty three percent of the respondents who felt that the cumulative achievement index received was relatively higher than the level of success of the knowledge gained. This shows the satisfaction obtained by students with the online learning system is relatively lower than that of the offline learning system. Keywords: offline learning, online learning, success, satisfaction